Tropospheric ozone decrease due to the Mount Pinatubo eruption: Reduced stratospheric influx. Issue 20 (28th October 2013) - Tang, Qi; Hess, Peter G.; Brown‐Steiner, Benjamin; Kinnison, Douglas E.
<x xml:space="preserve">Abstract</x> [1] We quantify the relationship between Mount Pinatubo eruption in June 1991 and tropospheric ozone abundances. The ozone reduction in the stratosphere and troposphere following the eruption is simulated by the Whole Atmosphere Community Climate Model and is in good agreement with the ozonesonde observations. Simulated anomalies in the global stratosphere‐troposphere flux of ozone following the eruption are well correlated with those in the tropospheric ozone column. Both are at their minimum in late 1992 to early 1993 (−70 Tgyr−1 in January 1993 for the flux and −1.9 Dobson Unit in November 1992 for tropospheric ozone) and recover after 1995. Therefore, this study identifies the reduced stratosphere‐to‐troposphere ozone flux as an important driver of the ozone decline in the troposphere following the eruption. A large fraction (67%) of the decrease in the flux is compensated by an increase in tropospheric photochemical ozone production. While both the strength of the residual circulation and the decrease in stratospheric ozone reduce the stratospheric ozone flux, the ozone reduction is identified as the dominant cause.